Variability of high dry matter orange-fleshed sweetpotato [Ipomoea batatas (L.) Lam.] in later breeding stages and allocation of breeding resources in the humid tropics of Peru - Díaz, F.; Eyzaguirre, R.; Marulanda, J.L.; Blas, R.; Longin, C.F.H.; Utz, H.F.; Boeck, B. de; Grüneberg, W.J. (Wiley, 2024)
Key message Variance-covariances in elite sweetpotato breeding material suggest an opportunity to combine high storage root yields, high root dry matter and high root β-carotene contents; optimized single-trait yield selection scenarios can serve as appropriate selection scenarios across yield and quality traits.